2020
DOI: 10.3389/fpls.2020.00761
|View full text |Cite
|
Sign up to set email alerts
|

Introgression Breeding in Barley: Perspectives and Case Studies

Abstract: Changing production scenarios resulting from unstable climatic conditions are challenging crop improvement efforts. A deeper and more practical understanding of plant genetic resources is necessary if these assets are to be used effectively in developing improved varieties. In general, current varieties and potential varieties have a narrow genetic base, making them prone to suffer the consequences of new and different abiotic and biotic stresses that can reduce crop yield and quality. The deployment of genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 93 publications
2
31
0
1
Order By: Relevance
“…For the agronomic traits, the lowest heritability was recorded for seed yield in our experiment, perhaps because yield is a character controlled by many genes. Moreover, as reported by Hernandez et al [ 14 ], the progress in selection for this trait is, in general, slow due to the masking effect of the environment and to a narrow germplasm base in barley. Furthermore, according to Yadav et al [ 20 ], we found a high heritability and a moderate genetic advance for the days to heading and thousand seed weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the agronomic traits, the lowest heritability was recorded for seed yield in our experiment, perhaps because yield is a character controlled by many genes. Moreover, as reported by Hernandez et al [ 14 ], the progress in selection for this trait is, in general, slow due to the masking effect of the environment and to a narrow germplasm base in barley. Furthermore, according to Yadav et al [ 20 ], we found a high heritability and a moderate genetic advance for the days to heading and thousand seed weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, very few naked barley cultivars have been developed for modern European and North American agricultural systems [ 13 ]. The introgression of the naked phenotype is currently an interesting goal of breeding to develop naked multi-use barley lines for conventional and organic systems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely studied crop model with abundant genetic resources that include diverse natural cultivated, wild and landrace collections, experimentally constructed populations, introgression and mutant lines. Its robust diploid genetics are supported by numerous high-resolution linkage maps and fully sequenced reference and pan-genome sequences (1, 2, 3, 4, 5). Genomic diversity has contributed to barley being grown worldwide, producing harvestable yields under a broad range of environmental conditions and climates (1, 4, 6).…”
Section: Background and Summarymentioning
confidence: 99%
“…Estos resultados abren la posibilidad de reorganizar el programa de mejoramiento con la tropicalización de la cebada, mediante la hibridación intraespecífica con énfasis en incrementar el potencial productivo y mejorar la calidad industrial del grano en las variedades locales antiguas. Esta estrategia, se utiliza con éxito con la introgresión (hibridación interespecífica) de germoplasma tropical del maíz en el temperado para mejorar adaptación en el trópico (Cairns & Prasanna, 2018) y en cebada para ampliar la base genética y la adaptación a estreses abióticos y la calidad (Hernandez et al, 2020).…”
Section: Discussionunclassified